Synthesis and characterisation of metal alloys for hydrogen storage and related applications - McGrath, Alexander John (2025)
This thesis investigates metal alloys for solid-state hydrogen storage, specifically the AB2 family, focusing on the methods used to synthesise hydrogen storage alloys, characterisation of the microstructures present, and the hydrogen storage properties relevant for stationary (energy storage and hydrogen compression) and mobile (light-duty passenger vehicles) applications. Throughout the thesis, the relationship between the processes used to synthesise a metal alloy, the observed microstructures and their effect on the measured hydrogen storage properties plays a critical role, and is frequently assessed and described. Metal alloys offer a safer, and more efficient mode of hydrogen storage compared to well-established storage methods, such as compressed gas or liquid hydrogen. They typically operate at lower pressures (1-50 bar) and provide high energy densities (95-160 kg H2/m3), however the main issue surrounding the use of metal alloys is the low gravimetric capacity that is usable in moderate conditions (1-2 wt.% at ca. 30◦C). Of the metal alloy families studied for solid-state hydrogen storage, the AB2 family offers the best hydrogen storage properties in moderate conditions (20-30 ◦C), such as gravimetric storage capacity (1.5-2 wt.%) and plateau pressure (5-50 bar). Many substitutions are available to fine-tune alloy properties, which could enable their use for a range of applications.